Expedited surgery in geriatric hip fracture patients taking direct oral anticoagulants is not associated with increased short-term complications or mortality rates. Issue 3 (21st September 2020) - Brown, Alexander; Zmich, Zachary; Roberts, Aaron; Lipof, Jason; Judd, Kyle T.
Abstract: Objectives: The purpose of this study was to evaluate potential differences in time to surgery, bleeding risk, wound complications, length of stay, transfusion rate, and 30-day mortality between patients anticoagulated with direct oral anticoagulants (DOACs) and those not anticoagulated at the time of evaluation for an acute hip fracture. Design: Retrospective chart review Level III Study. Setting: One university-based hospital in Rochester, NY. Patients/Intervention: : Patients 65 years and older undergoing operative treatment of a hip fracture over a 5-year period. Chart review identified patients on DOAC therapy at the time of injury as well as an age and sex-matched control group not on anticoagulation. Main outcome measurements: : Demographics, procedure type, admission/postoperative laboratory work, perioperative metrics, transfusion metrics, discharge course, reoperation, readmission, wound complications, and 30-day mortality were obtained for comparison. Results: Thirty-six hip fractures anticoagulated on DOACs were compared to 108 controls. The DOAC group had delays to operative treatment (27.6 h, SD 16.3 h, 95% CL [22.0–33.1]) vs the control group (19.8 h, SD 10.5 h, 95% CL [17.7–21.8], P = .01). No differences were found in estimated blood loss, procedure time, or change in hemoglobin. Transfusion rates were not significantly different between groups (58.3% DOAC vs 47.2% control, P = .25). No difference in reoperation, readmission, wound complication, deep venous thrombosis rates, or 30-day mortality rates were found. Conclusion: Patients presenting on DOAC therapy at the time of hip fracture have a delay to surgery compared with age and sex-matched controls, but no increase in short term complications or mortality rates. Expedited surgery (within 48 h) appeared to be safe and effective treatment for hip fracture patients on DOAC therapies.